PENGARUH SELF-EFFICACY DAN STRATEGI PEMBELAJARAN TEACHING FACTORY TERHADAP KESIAPAN KERJA SEKTOR PERKANTORAN PADA SISWA SMKN 10 SURABAYA - Al Baihaqi, Fatikhuddin; Ibadil Maula, Farij (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The work readiness of vocational high school (SMK) students is a crucial factor in producing graduates capable of meeting the needs of the business and industrial sectors. However, there are still SMK graduates who lack optimal work readiness, making it necessary to identify the factors that influence it. This study aims to analyze the influence of self-efficacy and Teaching Factory learning strategies on work readiness in the office sector among students in the Office Management Specialization Program at SMKN 10 Surabaya. The study employed a quantitative approach with an explanatory design. Data were collected through a questionnaire distributed to 11th-grade students who had participated in the Teaching Factory program and were then analyzed using multiple linear regression after meeting the validity, reliability, and classical assumption tests. The results indicate that self-efficacy has a positive and significant effect on work readiness; Teaching Factory learning strategies also have a positive and significant effect on work readiness; and both variables simultaneously have a positive and significant effect on students’ work readiness. These findings suggest that enhancing students’ self-efficacy through industry-based learning can improve the work readiness of vocational high school graduates. This study has implications for schools to strengthen the implementation of the Teaching Factory model and develop learning programs that can enhance students’ self-efficacy as part of an effort to produce graduates who are better prepared for the workforce.